I’m betrayed and I’m gone – unless organizational leaders convince me otherwise: Perceived contract breaches, quitting intentions, and leader-related resources - De Clercq, D.; Pereira, R. (Africa Journal of Management, 2023)
Employees’ perceptions that their organization has not met its promises toward them (i.e., perceived contract breaches) might inform their turnover intentions, in a link that also could be moderated by four relevant leader-related resources – two that reflect how organizational leaders share knowledge (communication efficiency and informational justice) and two that capture the nature of the relationship between employees and organizational authorities (humility and forgiveness). Using survey data collected among employees who operate in the oil distribution sector in Angola, this study shows that employees’ frustrations about broken organizational promises fuel their desire to quit their jobs, but less so when these employees believe that organizational leaders communicate efficiently and fairly, exhibit humility in their interactions with leaders, and perceive the leaders as forgiving. For organizations, these results provide novel insights into various conditions in which irritations about unmet expectations are less likely to escalate into a detrimental situation in which employees plan to leave.